Wages, house prices and industry composition: an empirical analysis of cities in China. Issue 4 (2nd October 2019) - Wang, Jing; Zhu, Lifen; Li, Jing
Abstract: Wages and house prices are two of the hottest public issues in China today. Whether and how the change in industry composition affects them? These issues have received widespread public attention. This study is dedicated to analysing the effects of industrial composition, which is measured by an index calculated using 19 2-digit industries, on wages and house prices using a modified hedonic price model and prefecture-level city data from China between 2005 and 2013. The main findings indicate that (1) an increase in industry composition index will drive up wages and house prices. The increment of wages surpasses that of house prices, showing that the house-purchasing burden decreases as the index increases; and (2) the effects of industry composition on wages and house prices differ between high-, middle- and low-income cities. The change in industry composition may increase the wage and house price gaps between cities of different income levels.